Ethical Analysis of Hermione's Behaviour in the Harry Potter Films - Chanthasatratsamee , Jatupong; Koolada, Thanakrit; Koeimat, Kritsada (BUDDHO, 2024)
This article aims to study the behavior of Hermione Granger from the Harry Potter film through ethical analysis. Ethics involves examining human behavior, studying values, criteria for judgment, and biases that affect human life, either positively or negatively. Decisions are often made based on ethical principles such as right or wrong, good or bad, should or shouldn’t. Understanding humans and the various aspects defined by them reveals that all criteria are human-made. Humans are born with needs, accompanied by motivations and stimuli that influence decision-making based on the reasoning they hold. This analysis particularly focuses on the well-known character Hermione Granger from the film “Harry Potter,” utilizing foundational ethical principles and Buddhist ethics. Ethical reasoning differs from religious principles, as it emphasizes understanding human reasons more profoundly, where good and evil are endlessly open to interpretation.And the actions that Hermione does in the fight for righteousness considered correct or not?”